Molecular Modeling of Anti-Alopecia Compounds Found in Sauropus Androgynus - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
People in the village of Mak Kemas, Malaysia use the katuk leaves (Sauropus androgynus) to prevent anti-alopecia. It was thought that katuk leaves have secondary metabolites which could accelerate the growth of new hair. The objective of this study was to determine the molecular modeling of compounds contained in katuk leaves (Sauropus androgynous) providing docking and ADMET information in silico as anti-alopecia drugs. In this study, receptors were used (PDB code: 4K7A) derived from protein data banks (http://www.rscb.org/pdb) and visualized with Discovery Studio and tested 10 compounds that had the potential as ligands to prevent baldness. Molecular modeling of bioactive compounds was carried out by molecular docking computation using AutodockTools 1.5.6 and Pre-Admet to determine absorption, distribution, and toxicity. The results were an amino acid residue that showed the place-bound to the receptor, inhibitory constant (Ki), and free energy bonds (∆ G). Of the 11 compounds studied, 3 were 5-Alpha-Dihydrotestosterone; Finasteride; and Pyrene interacts well so that it could prevent baldness. From the results of docking and pre-admet that had been done, it concluded that the compounds contained in katuk leaves could be used as candidates for anti-alopecia drugs.Keywords: Anti-alopecia, ADMET, In-silico, Katuk Leaf, Sauropus androgynus.